Pengaruh efisiensi dan kredit bermasalah terhadap modal kerja pada PT Bank Pembangunan Daerah Banten tbk periode 2011- 2021 - Akbar, Akhmad (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
The purpose of this study was to determine whether there is a significant influence between the Efficiency and Non-Performing Credit variables on Working Capital at PT. Banten Regional Development Bank Tbk Period 2011-2021. This research is a descriptive analysis study with a quantitative method approach. The type of data used in this study is secondary data obtained from financial reports published at PT Bank Pembangunan Daerah Banten Tbk from the Indonesia Stock Exchange (IDX) for the period 2011 to 2021. Data collection techniques using classical assumption test techniques, multiple linear regression analysis techniques, hypothesis testing with the methods used are literature, documentation and calculations with the SPSS version 26 program. From this test either partially or simultaneously there is no effect and it is not significant between variables Efficiency and non-performing loans to working capital at PT Bank Pembangunan Daerah Banten Tbk for the 2011-2021 period.